MENILIK KINERJA PEGAWAI KANTOR CAMAT DI NIAS SELATAN YANG DIPENGARUHI LINGKUNGAN KERJA DAN STRES KERJA - Duha, Timotius (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
This research intends to find out how much the work environment and work stress influence the performance of sub-district office employees in South Nias. This research is quantitative in type. In this research, the population came from employees in three large sub-district offices in South Nias (Telukdalam, Fanayama, and Amandraya). The sample used was total sampling. So the total sample is 8219 people. Data collection is through distributing questionnaires which are then filled in with answers by respondents. Data analysis uses multiple linear regression. Research findings show: partially or simultaneously, the two independent variables have a positive influence on the dependent variable. The main recommendation for this research is the need to add other topics that can increase performance, such as job satisfaction.